The Current Development of Marriage Age Provisions in Indonesia and Malaysia: A Socio-Historical Approach - Ibnu Radwan Siddik Turnip; Zainul Fuad; Nurhayati Nurhayati; Ibnu Radwan Siddik (IAIN Manado, 2022)
This paper discusses how the current social history of Islamic law in the Southeast Asian region relates to the minimum age of marriage. Then also, it will be examined how socio-cultural and socio-political influences surround the change in the provisions of the minimum age of marriage in the two countries. This normative legal research focused on studying legal history using the social history approach of Islamic law. Data is analyzed with qualitative methods. The results showed a change in the age of marriage in Indonesia, from 19 years for men and 16 years for women to 19 years for both men and women. While in Malaysia, most states have not changed the minimum age of marriage, remaining at 18 years old for men and 16 years for women. The change in the age of marriage occurs in the state of Selangor alone, which determines the marriage age limit is 18 years for men and women. The difference in terms of the marriage age limit in these two countries is strongly influenced by the socio-cultural and socio-political dynamics in society. The aspirations of some groups of people towa rds changing the marriage age limit in both countries have also strengthened due to the growing number of cases of child marriage, extramarital pregnancy, and the practice of abortion in both countries.